1982
DOI: 10.1177/019459988209000222
|View full text |Cite
|
Sign up to set email alerts
|

Stapes Prosthesis Comparison

Abstract: Ninety-four consecutive stapedectomy cases using the Robinson stainless steel prosthesis are compared with 100 consecutive cases using the House stainless steel wire prosthesis. The air-bone gap was closed to within 10 dB in 94% of the cases with the Robinson prosthesis and in 88% of the cases using the House stainless steel wire prosthesis. There appeared to be no difference in the improvement at 2,000 and 4,000 cycles between the two techniques and the results were the same. Statistical study revealed there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In our study, 91% of all patients had an air–bone gap of not more than 20 dB with 60% of our patients having an air–bone gap of not more than 10 dB. Comparable studies have reported good results in 84–95% 10,12 and an ‘excellent’ result in 50–79% 10–16 . Some of these authors calculated the postoperative air–bone gap by the use of the pre‐operative bone conduction threshold and the postoperative air conduction threshold 13,15,16 .…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In our study, 91% of all patients had an air–bone gap of not more than 20 dB with 60% of our patients having an air–bone gap of not more than 10 dB. Comparable studies have reported good results in 84–95% 10,12 and an ‘excellent’ result in 50–79% 10–16 . Some of these authors calculated the postoperative air–bone gap by the use of the pre‐operative bone conduction threshold and the postoperative air conduction threshold 13,15,16 .…”
Section: Discussionmentioning
confidence: 47%
“…Comparable studies have reported good results in 84-95% 10,12 and an 'excellent' result in 50-79%. [10][11][12][13][14][15][16] Some of these authors calculated the postoperative air-bone gap by the use of the pre-operative bone conduction threshold and the postoperative air conduction threshold. 13,15,16 This makes a great difference.…”
Section: Discussionmentioning
confidence: 99%
“…However, using wire loops, manual crimping is key and includes the risk of failure of surgery. A new self‐retaining clip prosthesis was developed by Wengen 12 to circumvent crimping. The trade‐off of this prosthesis is the relatively clumsy shape of the clip compared to the elegant classic prosthesis loop, which allows individual adaptation to anatomical variations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a self‐retaining clip prosthesis 7 as well as a self‐crimping shape memory alloy Nitinol stapes piston 8 is an alternative technique with largely unknown long‐term outcomes. Therefore, wire loop prostheses of different materials are most commonly used in stapes surgery with reliable, safe, and consistent air‐bone‐gap closure 1,9–13 . However, using a standard crimper, two problems often occur and can result in manual malcrimping as well as incus luxation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, revision surgery is connected with higher risks, as profound sensorineual hearing loss, dizziness, etc. (3,4,5). It is generally known that the rate of successful surgical procedure, evaluated as closure of air-bone gap less than 10 dB ranges between 20-85 % (6, 7).…”
mentioning
confidence: 99%